Classificação supervisionada com programação probabilística - Lucena, Danilo Carlos Gouveia de (2014)
Probabilistic inference mechanisms are at the intersection of three main areas: statistics, programming languages and probability. These mechanisms are used to create probabilistic models and assist in treating uncertainties. Probabilistic programming languages assist in high-level description of these models. These languages facilitate the development of the models because they abstract the inference mechanisms at the lower levels, allow reuse of code, and assist in results analysis. This study proposes the analysis of inference engines implemented by probabilistic programming languages and presents a case study of a supervised text classifier using probabilistic programming.